Metode Pembiasaan Majlis Pagi Dalam Menanamkan Pendidikan Karakter Religius Di RA At-Taufiq Kota Tasikmalaya - Musaadah, Silpi; Nugraha, Dadan; Maulana Rizki, Anggi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to describe the implementation of the habituation method in shaping the religious character of early childhood students at RA At-Taufiq. This research uses a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. The results show that the Majlis Pagi (Morning Assembly) activity, as a form of habituation, includes recitation of iqra, memorization of prayers, hadiths, short surahs, and the practice of dhuha prayer. These activities are conducted consistently every morning and have become part of the school program. Teachers play a crucial role in delivering material appropriate to the child’s developmental stage through the talaqqi method, exemplary behavior, and personal approaches. In addition, parental involvement and family background are both supporting and inhibiting factors in the implementation of this activity. The habituation method proves to be effective in instilling religious values from an early age, although there are still challenges such as children’s lack of focus and delays in attendance due to parenting patterns at home. The uniqueness of the morning assembly as a religious haracter building program lies in its routine, structured, and enjoyable implemetation, so that children can intrnalize religus values without coercion. Through activities such as joint prayer, greetings, and memorizing short verses, children learn directly from the teacher’s example, forming fositive habits as from an early age. The morning assembly also creates a distinctive spiritual atmosphere and becomes an effective medium and fostering a religiuous attitude naturally and consistenly